ASOD Coordination In Overcoming Drug Smuggling: A Multilevel Governance Approach - Yosefa Amelia; Novita Putri Rudiany (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2026)
The ASEAN Senior Officials on Drug Matters (ASOD) is a regional cooperation forum for Southeast Asia to coordinate efforts to achieve a “Drug-Free” ASEAN. Drug smuggling at the Entikong Indonesia-Malaysia border is one of many crucial issues. This study analyzes multilevel governance interactions within the ASOD framework for the 2010-2015 period using qualitative methods. The focus includes vertical, horizontal, and collaborative dynamics between actors at the regional and local levels. An in-depth analysis of multilevel governance interactions in drug handling is conducted, which is a dynamic reciprocal process that demands active coordination and policy adjustments from the regional to sub-national levels. The results of the study indicate that this multilevel governance has significant potency to create a more adaptive and responsive drug countermeasure strategy in border areas.